Spatial and environmental analysis of Mycobacterium avium infected dairies in Antioquía (Colombia) (2021)
ABSTRACT: The present study aimed to describe the spatial distribution of Mycobacterium avium subsp. paratuberculosis (MAP) in dairy herds, and to detail environmental variables taken as reference of the physical background of the study area, specifically those related to MAP-qPCR positive herds located in six municipalities of the northern region of the Province of Antioquia (Colombia), based on environmental sampling and qPCR analysis. The study herds (n= 386) were located in 63 different districts from six municipalities. Participant herds were visited once between June and October (2016) to collect an environmental sample, and identification of MAP was achieved using a duplex quantitative real-time PCR method. Rainfall trends, day and nighttime surface temperature, and vegetation cover index were taken as environmental references of the physical background of the study area. In addition, distribution maps of MAP-qPCR positive and negative herds, as well as maps of temperature variations and vegetation cover, were constructed. As a result, there was an increase in MAP-positive herds in the North-West, South, and Southeast of the study area. An overall high rainfall regime was found and day- and nighttime surface temperatures showed important variations during sampling months. No evidence of management of the vegetation cover was found, in both pastures and areas with native vegetation, except for a conservancy area. In conclusion, the general environmental conditions, where the detection of MAP-positive herds is most likely to happen, were reported herein, considering approaches using the same (or a very approximate) sample collection and handling, and molecular detection method.